2023
DOI: 10.1097/corr.0000000000002573
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram That Characterizes a Patient’s Odds of Developing Squeaking After Fourth-generation Ceramic-on-ceramic THA

Abstract: Background Although ceramic-on-ceramic (CoC) bearings result in the lowest wear rate of any bearing combination, postoperative squeaking remains worrisome. However, data concerning squeaking in long-term follow-up studies are still lacking, especially for fourth-generation CoC THA. Questions/purposes (1) After keeping the prosthesis in place for 10 years, what percentage of patients treated with fourth-generation CoC THA implants report squeaking, and are there points in time when squeaking occurs more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the current study, Li et al [6] found that 16% (116 of 726) of patients reported squeaking over the 10-year study, with demographic peaks occurring in the first year after surgery and between 8 and 10 years afterward; of those who had squeaking, 42% (36 of 86) reported it frequently. The authors also developed and shared a useful nomogram that can help clinicians identify patients at a higher risk of experiencing squeaking based on factors like age, ROM, and implant offset.…”
Section: Where Are We Now?mentioning
confidence: 48%
“…In the current study, Li et al [6] found that 16% (116 of 726) of patients reported squeaking over the 10-year study, with demographic peaks occurring in the first year after surgery and between 8 and 10 years afterward; of those who had squeaking, 42% (36 of 86) reported it frequently. The authors also developed and shared a useful nomogram that can help clinicians identify patients at a higher risk of experiencing squeaking based on factors like age, ROM, and implant offset.…”
Section: Where Are We Now?mentioning
confidence: 48%
“…We read with great interest the publication by Li et al, “A Nomogram That Characterizes a Patient’s Odds of Developing Squeaking After Fourth-generation Ceramic-on-ceramic THA” [6]. The authors found that squeaking is a potential late complication after fourth-generation ceramic-on-ceramic (CoC) THA, and they recommend using a nomogram to assess patients’ risk of developing this problem.…”
mentioning
confidence: 99%
“…The combination of high acetabular component inclination (>55°) and high anteversion (>25°) seemed to result in increased wear and an increased risk of anterior-superior edge loading. Orientation of the cup and stem with other nomogram parameters may be responsible for the first peak of squeaking; however, for patients who develop late squeaking (the second demographic peak, which accounted for 48% of patients who developed this problem, according to the CORR ® paper [6]), the mechanism is unclear. Stripe wear and edge loading are possible mechanisms for late squeaking.…”
mentioning
confidence: 99%
See 1 more Smart Citation